Recycling photovoltaic modules: a sustainable approach to renewable energy - Hiranobe, Márcia Ferreira (2024)
The growing demand for clean energy has driven the expansion of photovoltaic solar energy, leading to an increase in the number of installed solar panels. However, the improper disposal of solar panels can result in negative environmental impacts. Therefore, the recycling of photovoltaic panels emerges as a critical alternative to mitigate these effects. This review article aims to present the currently available solar panel recycling techniques and discuss the challenges and future perspectives of this practice. The methodology was based on searches in the Scopus, Web of Science, and Google Scholar databases to identify relevant articles on solar panel recycling. The findings highlight the necessity of combining mechanical methods with chemical and physical processes to achieve high-quality recycled materials. Furthermore, the study emphasizes the importance of implementing public policies and raising societal awareness about the significance of solar panel recycling to make this practice more widespread and effective.